The Effect of Platinum Based Bimetallic Electrocatalysts on Oxygen Reduction Reaction of Proton Exchange Membrane Fuel Cells - Hyun, Kyuhwan; Lee, Jin Hee; Yoon, Chang Won; Kwon, Yongchai (ESG, 2013)
Carbon supported PtM (M = Ni, Co, Cu and Y) alloy catalysts (PtM/Cs) are synthesized by reduction of metal precursors using sodium borohydride. With the PtM/Cs adopted as cathodic catalyst for proton exchange membrane fuel cells (PEMFCs), their oxygen reduction reaction (ORR) activity, catalytic stability and electrical performance are evaluated and compared with those of commercial Pt/C. Their crystal structure and elementary composition are measured by XRD, EDX and TEM. The measurements show that PtM/Cs have similar particle size to Pt/C and moderate PtM alloying degree. For evaluating ORR activity, catalytic stability and electrical performance, cyclic voltammetry, rotating disk electrode and PEMFC single cell tests are used. In terms of catalytic stability, PtM/Cs are more stable than Pt/C. It is probably due to higher adsorption energy for oxygen-M bond and lower MM bond energy. In ORR activity and electrical performance tests, PtNi/C shows better limiting current density, kinetic current density, half wave potential, reduction peak potential and maximum power density than Pt/C despite less amount of Pt in PtNi/C than that in Pt/C. However, when the measurements are analyzed as per gram Pt, all the PtM/C catalysts indicate better results than Pt/C, turning out that Pt particles in PtM/C are more effectively utilized than those in Pt/C.
Keywords: PT-M M; METAL-FREE ELECTROCATALYSTS; ORR ACTIVITY; ENHANCED STABILITY; CARBON NANOTUBES; ALLOY CATALYSTS; CO; FE; GRAPHENE; NI